Evaluating the effect of crop rotations and tillage practices on soil water balances of selected soils and crop performances in the Western Cape - Swiegelaar, Nina Antionette (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScAgric)--Stellenbosch University, 2014.